Passing through Identities: Artistic Mediation in the Rehabilitation Process of People with Addiction Problems - Moreno González, Ascensión; Usán, Sonia; Criado, Carlos; Santaforentina, Alejandro (Cuadernos de Trabajo Social, 2013)
During 2010 y 2011, two volunteers, students from the Faculty of Fine Arts from the University of Barcelona, have developed a project in a support center for people with addiction problems. This center is Centre d’Atenció i Seguiment (CAS) in Sants district from Barcelona. In this article we present the theoretical framework and the experiences in order to substantiate how artistic experience contributes to the process of social reintegration of these individuals.
Keywords: artistic mediation; volunteering; identity; drug-related problems; social reintegration